2021
DOI: 10.3389/fonc.2021.706428
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in HOTAIR Are Related to Breast Cancer Risk and Prognosis in the Northeastern Chinese Population

Abstract: BackgroundThe long noncoding RNA HOX transcript antisense RNA (HOTAIR) is highly expressed in breast cancer (BC) tissues and is associated with the recurrence and metastasis of BC. Until now, the results of studies on associations between several functional single nucleotide polymorphisms(SNPs) (rs920778, rs1899663, and rs4759314) in HOTAIR with BC susceptibility carried out in different regions of China are still inconsistent. There is no study on correlation between HOTAIR SNPs and prognosis of Chinese popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…A recent study analyzed the in situ expression of HOTAIR in breast cancer patients and showed that a high expression of HOTAIR in tumor tissue is closely related to lymph node metastasis [ 5 ]. A population-based case-control study found that HOTAIR is associated with breast cancer risk and prognosis [ 6 ]. Based on the important role of HOTAIR in breast cancer progression, a recent review summarized the potentially promising therapeutic function of HOTAIR in breast cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analyzed the in situ expression of HOTAIR in breast cancer patients and showed that a high expression of HOTAIR in tumor tissue is closely related to lymph node metastasis [ 5 ]. A population-based case-control study found that HOTAIR is associated with breast cancer risk and prognosis [ 6 ]. Based on the important role of HOTAIR in breast cancer progression, a recent review summarized the potentially promising therapeutic function of HOTAIR in breast cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, we reported a strong association of rs920778 G > A with increased CRC risk in the Saudi population, and a potential biomarker, the homozygous mutant genotype “AA”, showed a significant association with the risk of CRC, particularly with gender, age, and location. Some previous studies have reported the association of rs920778 SNP with increased cancer risk in Turkish, Indian, and Chinses populations [ 32 , 34 , 45 ]. Recently, HOTAIR rs920778 polymorphisms with higher survival rates were reported in CRC patients from South Korea [ 19 ] and in breast cancer patients in southeast Iran [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 33 ] reported that rs1899663 (G > T) increased lung cancer risk in China, and Hassanzarei et al [ 46 ] reported a negative association of rs1899663 (G > T) with breast cancer in Iran. Additionally, rs1899663 polymorphism is linked with breast cancer risk in Indian and Chinese populations and prostate cancer susceptibility in the Iranian population [ 32 , 34 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNPs) are reported to upregulate HOTAIR expression and are correlated with an increased risk of BC. In addition, the GG/AG genotype of rs720778 and GA genotype of rs4759314 are reported to be associated with lower disease-free survival (DFS) and overall survival (OS) and DFS, respectively, in some populations of BC patients [ 83 ]. A similar study in India by Rajagopal et al [ 84 ] reported that a combination of SNPs in NME1 (rs16949649 T > C and rs2302254 C > T) and HOTAIR (e.g., rs920778 C > T and rs1899663 G > T) increased the risk of BC in premenopausal women carrying mutant alleles.…”
Section: The Role Of Hotair In Breast Cancer Managementmentioning
confidence: 99%